Enhancing Auction Execution: Implementation Strategies For Collection Rights Auction Objects - Efrianza, Efrianza; Busro, Ahmad; Silviana, Ana (Universitas Widya Gama Malang, 2024)
Banking institutions play a crucial role in facilitating access to additional capital for businesses. As creditors, banks provide credit loans, and borrowers must fulfill certain conditions set by the bank to secure the loan. However, the transfer of claim rights through auctions, specifically for billing rights in the form of receivables, presents potential challenges. After the auction, the debtor becomes connected to the auction buyer as the new creditor, which may lead to irregularities in credit payments and potential losses for the bank. This research focuses on addressing the issues surrounding the execution of credit auctions and the subsequent management of non-performing loans. By examining different types of auctions, including execution auctions, district court execution auctions, and voluntary non-execution auctions, we aim to identify potential problems and devise effective strategies for credit recovery. Our findings will provide valuable insights for banks to mitigate risks, restore credit performance, and optimize loan recovery processes.